PENGEMBANGAN MODUL PEMBELAJARAN IPA MATERI PENCEMARAN LINGKUNGAN UNTUK SISWA KELAS VII MADRASAH TSANAWIYAH SWASTA PERGURUAN GUPPI PEMATANG SIANTAR - Dewi Purwanti, Ratih; Damanik, Risjunardi; Mustika Piliang, Fenny (Program Studi Pendidikan Biologi, Fakultas Keguruan Dan Ilmu Pendidikan Universitas Simalungun, 2023)
This research aims to develop a science learning module for seventh-grade students. This learning module aims to improve student learning outcomes and understanding of environmental pollution. This research is a type of research and development or Research and Development (R&D) with reference to Sugiyono's opinion. The product developed based on the initial research is a science learning module for seventh grade students containing environmental pollution material in the form of understanding, causes, types, impacts and efforts to overcome environmental pollution. The trial subjects in this research and development are media experts/lecturers, science teachers and seventh grade students of MTs Swasta Perguruan Guppi Pematang Siantar as potential product users. The sampling used in conducting this research is purposive sampling because the education system implemented at MTs Swasta Perguruan Guppi Pematang Siantar is a block system. Data collection techniques are carried out by interviews, questionnaires and tests. Interviews are used to obtain the required information, questionnaires are used to obtain the required information and student responses regarding the developed module and tests are used to determine the improvement in learning outcomes and student understanding of environmental pollution material. Data are analyzed qualitatively and quantitatively. The results of the study show that the science learning module trial for seventh grade MTs students is included in the good category. After revision, the science learning module trial results are included in the good category. Thus, the learning module This developed science module for seventh-grade MTs students is suitable for use by students.